2018
DOI: 10.1039/c7fo01928a
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble compounds ofRosmarinus officinalisL. improve the oxidative and inflammatory states of rats with adjuvant-induced arthritis

Abstract: Anti-inflammatory and antioxidant properties have been attributed to constituents of Rosmarinus officinalis. Considering the inflammatory nature of arthritis and the oxidative stress induced by the disease, this work aimed to investigate if R. officinalis is able to attenuate oxidative and inflammatory injuries caused by the disease. Rats with complete Freund's adjuvant induced arthritis were used. An aqueous extract of the rosemary leaves was administered orally. The parameters related to oxidative stress wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Despite the consequences following depression are serious, effective antidepressant drugs are limited. Rat experiments have demonstrated that RE owned effective anti-inflammatory function ( de Almeida Goncalves et al, 2018 ). However, no study has highlighted the antidepressant effects of RE on CRS mice, and the inflammatory mechanisms related to gut microbiome have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the consequences following depression are serious, effective antidepressant drugs are limited. Rat experiments have demonstrated that RE owned effective anti-inflammatory function ( de Almeida Goncalves et al, 2018 ). However, no study has highlighted the antidepressant effects of RE on CRS mice, and the inflammatory mechanisms related to gut microbiome have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The main constituent, rosmarinic acid ( Figure 1 A), is a naturally occurring hydroxylated polyphenol molecule found in several plant families, including Lamiaceae , Boraginaceae , and Blechnaceae [ 11 , 12 ]. It has been shown to have antioxidant, anti-inflammatory, anti-viral, anti-mutagenic, and anti-angiogenic capabilities [ 9 , 10 , 13 , 14 , 15 , 16 , 17 ]. Moreover, rosmarinic acid appears to be neuroprotective and has been demonstrated to induce neuroprotection from reactive glial cells in in vitro models of AD, spinal cord injury, and PD by inhibiting nitric oxide (NO) production [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…4- O -caffeoylquinic acid (2 isomers), medioresinol (phenolic lignin), caffeic acid and rosmarinic acid (2 isomers) were the identified phenolic acids, whereas the flavonoid compounds found were glycoside derivates of luteolin (5 compounds), isorhamnetin (2 compounds) and quercetin (1 compound). All the mentioned compounds, with the exception of the phenolic lignin and isorhamnetin glycoside derivatives, have been previously described by the authors in other studies involving R. officinalis [ 19 , 20 , 21 ]. Thus, peak 3 ([M − H] − ion at m / z 387) presented two main MS 2 fragment ions at m/z 207 and 163, being tentatively identified as medioresinol, taking into account data reported in the literature [ 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%